2001
DOI: 10.1074/jbc.m103531200
|View full text |Cite
|
Sign up to set email alerts
|

Biophysical Characterization of Interactions Involving Importin-α during Nuclear Import

Abstract: Proteins containing the classical nuclear localization sequences (NLSs) are imported into the nucleus by the importin-␣/␤ heterodimer. Importin-␣ contains the NLS binding site, whereas importin-␤ mediates the translocation through the nuclear pore. We characterized the interactions involving importin-␣ during nuclear import using a combination of biophysical techniques (biosensor, crystallography, sedimentation equilibrium, electrophoresis, and circular dichroism). Importin-␣ is shown to exist in a monomeric a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

28
130
1

Year Published

2003
2003
2016
2016

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 144 publications
(159 citation statements)
references
References 52 publications
28
130
1
Order By: Relevance
“…Generation of Mutant Importin ␣ Proteins-Previous structural and in vitro analyses identified an auto-inhibitory sequence within the N-terminal IBB domain of importin ␣ (23,24,26). The structural studies suggested that this auto-inhibitory domain interacts with the NLS binding pocket by mimicking an NLS sequence (23,24).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Generation of Mutant Importin ␣ Proteins-Previous structural and in vitro analyses identified an auto-inhibitory sequence within the N-terminal IBB domain of importin ␣ (23,24,26). The structural studies suggested that this auto-inhibitory domain interacts with the NLS binding pocket by mimicking an NLS sequence (23,24).…”
Section: Resultsmentioning
confidence: 99%
“…In support of this hypothesis, in vitro binding studies have shown that importin ␣ lacking the proposed auto-inhibitory domain (⌬IBB-␣), binds more tightly to NLS-cargo than full-length importin ␣ (26), and that this auto-inhibition of full-length importin ␣ binding to NLS-cargo is relieved in the presence of importin ␤ (17,26). Further analysis of the N-terminal IBB domain of importin ␣ revealed a proposed internal NLS that could serve as an autoinhibitory sequence to regulate NLS binding through intramolecular competition for the NLS binding site (23,24). Taken together, these studies suggest a dual role for the N-terminal domain of importin ␣ in 1) binding to importin ␤ and 2) autoinhibition of NLS-cargo binding.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The strongest affinities of natural ArmRPs were reported to be in the range of 20 nM for importin-α binding to NLS peptides [27,28]. From an initial version of a consensus ArmRP library, a binder to neurotensin was selected with a K d of 7 µM [29], but the binding mode was different from the intended canonical binding [30].…”
Section: Surface Redesign For Peptide Bindingmentioning
confidence: 99%
“…Fluorescent cargo concentrations were ≥ 100 nM in ensemble (bulk) experiments, and ∼100 pM for single molecule transport assays. At these cargo and cofactor concentrations, >99% of the cargo was expected to be complexed with importin-α and importin-β [33].…”
Section: Transport Cofactors and Ensemble Transport Experimentsmentioning
confidence: 99%